Enhancing Students’ Emotional Intelligence in Biology Through Scaffolding-Enriched Diagnostic Assessment in Benue State - Kpiranyam, Felix Sesugh; Agogo, Peter Ogbu; Ode, Jackson Ochigbudu; Abah, John Clement (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The study was an attempt to enhance secondary school students’ emotional intelligence in Biology through scaffolding-enriched diagnostic assessment techniques in Benue State. Three questions were answered and three hypotheses tested at 0.05 level of significance. This study utilized a quasi-experimental design characterized by a non-randomized pre-test and post-test control group framework. Population comprised 19,357 Senior Secondary Two (SS II) students, 10,273 males and 9,084 females, enrolled in Biology across 183 public co-educational schools. Sample comprised 245 (153 males and 92 females) students. Students’ Emotional Intelligence Questionnaire in Biology (SEIQB) was developed by the researchers and validated by a panel of three experts. It had reliability value of 0.92 determined using Cronbach’s Alpha. Three research assistants taught the three groups, Scaffolding-enriched Diagnostic Assessment with Feedback and Remediation (SDAFR) Scaffolding-enriched Diagnostic Assessment with Feedback (SDAF) and Scaffolding-enriched Conventional Assessment (SCTA) and administered the instrument. Data were analyzed using mean and standard deviation (SD) to address the research questions. Analysis of Covariance (ANCOVA) was employed to test the null hypotheses. Bonferroni’s post hoc analysis was also used. The results revealed a significant difference in the mean emotional intelligence ratings of Biology students exposed to SDAFR, SDAF, and SCTA (F(3, 241) = 6.080, p = 0.003 < 0.05). Post hoc bivariate comparisons indicated significant differences (p < 0.05) between SDAFR and SDAF, and between SDAFR and SCTA, while no significant difference was observed between SDAF and SCTA (p > 0.05). Furthermore, findings showed no significant difference in the mean emotional intelligence ratings between male and female Biology students exposed to SDAFR (F(2, 72) = 0.916, p = 0.342 > 0.05) or SDAF (F(2, 88) = 2.778, p = 0.099 > 0.05). Based on these findings, it is recommended, among others that Biology teachers adopt SDAFR to enhance students’ emotional intelligence in Biology.